(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This study enhances the piezoelectric effects of electrospun nanocomposite nanofibers formed from layers of PVDF-Ceramic nanogenerator. Through the use of several side nanocomposites, the nanogenerator has evolved from a single to a double layer. The outputting piezoelectric is very highly dependent on fabricated performance. A researcher has previously demonstrated interest in mixed nanocomposites (PZB) that are capable of enhancing performance and boosting output voltage to 7,200 V by applying 0.2657 N of force and 2.5 Hz of frequency. Thus, fabricate thin generator companion of nanocomposite materials fibers together with concentrations (16%PVDF– 18%ZnO) and (12%PVDF–20%BaTiO3). The phase transition of this generator is detailed using XRD, SEM, and FTIR, and its electrical response characteristics are assessed using an oscilloscope